Britannia's palette : the arts of naval victory - Tracy, Nicholas, 1944- (McGill-Queen's University Press, 2007)
Britannia's Palette looks at the lives of British artists who witnessed the naval war against the French Republic and Empire between 1793 and 1815. This band of brothers, through their artistic and entrepreneurial efforts, established the images of the war at sea that were central to the understanding their contemporaries had of events - images that endure to this day.